Diaphragmatic hernias after pediatric liver transplantation: Experience of a high‐volume transplant center. (12th March 2020) - Karakas, Serdar; Sahin, Tevfik Tolga; Kutluturk, Koray; Otan, Emrah; Baskiran, Adil; Sarici, Kemal Baris; Varol, Ilknur; Aydin, Cemalettin; Kayaalp, Cuneyt; Yilmaz, Sezai
Abstract: Diaphragmatic hernias (DHs) are rare complications after pediatric liver transplantation (PLT). It is now widely accepted that DHs after liver transplantation (LT) is a pediatric related condition. PLTs (under of age 18) performed between January 2013 and June 2019 at Malatya Inonu University Institute of Liver Transplantation were retrospectively scanned. Study group consisting DHs and a control group were compared. Among 280 PLTs, 8 of them were complicated with DHs (%2.9). Median age of the patients with DH was 3.0 (0.8‐9.5) years. Median graft recipient weight ratio was 2.5 (0.9‐4.4). Five patients were below 5th percentiles in terms of pediatric weight growth chart at the time of LT. Also, 6 patients were below 5th percentiles in terms of pediatric height growth chart. There was no statistical difference between study and control groups. There are many risk factors mentioned in literature that may be primarily responsible for DHs after PLT. These factors are left lobe and large‐for‐size grafts, malnutrition, trauma or diathermy of diaphragmatic nerve and vessels and immunosuppressants. In our study, we could not specify any reason that differs in DHs. In our aspect, narrow diaphragma and thorax are exposed to high intra‐abdominal pressure from abdomen. Large‐for‐size grafts, which are specific to children, also may contribute to this affect. Excessive diathermy and trauma to diaphragmatic collaterals may aggravate the risk of DH. More patients are needed to make an exact conclusion, in order to evaluate with comparable study on this aspect.